-4k(k+6)-(9k-6)=-14k

Simple and best practice solution for -4k(k+6)-(9k-6)=-14k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4k(k+6)-(9k-6)=-14k equation:


Simplifying
-4k(k + 6) + -1(9k + -6) = -14k

Reorder the terms:
-4k(6 + k) + -1(9k + -6) = -14k
(6 * -4k + k * -4k) + -1(9k + -6) = -14k
(-24k + -4k2) + -1(9k + -6) = -14k

Reorder the terms:
-24k + -4k2 + -1(-6 + 9k) = -14k
-24k + -4k2 + (-6 * -1 + 9k * -1) = -14k
-24k + -4k2 + (6 + -9k) = -14k

Reorder the terms:
6 + -24k + -9k + -4k2 = -14k

Combine like terms: -24k + -9k = -33k
6 + -33k + -4k2 = -14k

Solving
6 + -33k + -4k2 = -14k

Solving for variable 'k'.

Reorder the terms:
6 + -33k + 14k + -4k2 = -14k + 14k

Combine like terms: -33k + 14k = -19k
6 + -19k + -4k2 = -14k + 14k

Combine like terms: -14k + 14k = 0
6 + -19k + -4k2 = 0

Begin completing the square.  Divide all terms by
-4 the coefficient of the squared term: 

Divide each side by '-4'.
-1.5 + 4.75k + k2 = 0

Move the constant term to the right:

Add '1.5' to each side of the equation.
-1.5 + 4.75k + 1.5 + k2 = 0 + 1.5

Reorder the terms:
-1.5 + 1.5 + 4.75k + k2 = 0 + 1.5

Combine like terms: -1.5 + 1.5 = 0.0
0.0 + 4.75k + k2 = 0 + 1.5
4.75k + k2 = 0 + 1.5

Combine like terms: 0 + 1.5 = 1.5
4.75k + k2 = 1.5

The k term is 4.75k.  Take half its coefficient (2.375).
Square it (5.640625) and add it to both sides.

Add '5.640625' to each side of the equation.
4.75k + 5.640625 + k2 = 1.5 + 5.640625

Reorder the terms:
5.640625 + 4.75k + k2 = 1.5 + 5.640625

Combine like terms: 1.5 + 5.640625 = 7.140625
5.640625 + 4.75k + k2 = 7.140625

Factor a perfect square on the left side:
(k + 2.375)(k + 2.375) = 7.140625

Calculate the square root of the right side: 2.672194791

Break this problem into two subproblems by setting 
(k + 2.375) equal to 2.672194791 and -2.672194791.

Subproblem 1

k + 2.375 = 2.672194791 Simplifying k + 2.375 = 2.672194791 Reorder the terms: 2.375 + k = 2.672194791 Solving 2.375 + k = 2.672194791 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2.375' to each side of the equation. 2.375 + -2.375 + k = 2.672194791 + -2.375 Combine like terms: 2.375 + -2.375 = 0.000 0.000 + k = 2.672194791 + -2.375 k = 2.672194791 + -2.375 Combine like terms: 2.672194791 + -2.375 = 0.297194791 k = 0.297194791 Simplifying k = 0.297194791

Subproblem 2

k + 2.375 = -2.672194791 Simplifying k + 2.375 = -2.672194791 Reorder the terms: 2.375 + k = -2.672194791 Solving 2.375 + k = -2.672194791 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2.375' to each side of the equation. 2.375 + -2.375 + k = -2.672194791 + -2.375 Combine like terms: 2.375 + -2.375 = 0.000 0.000 + k = -2.672194791 + -2.375 k = -2.672194791 + -2.375 Combine like terms: -2.672194791 + -2.375 = -5.047194791 k = -5.047194791 Simplifying k = -5.047194791

Solution

The solution to the problem is based on the solutions from the subproblems. k = {0.297194791, -5.047194791}

See similar equations:

| 3x+2.5x=60 | | P=2(1.08)t | | 4.9t^2+17.9t+5=0 | | 12.8*0.25= | | X-90=4x | | 5a=7+8a | | 4x-2(x-4)=-6+4x+10 | | (10x^2+30x)=(2x^2-30x-75) | | -2x+5(-2x-6)=18 | | 3-(6s-15)=4s+8 | | 20x^2+25x+75=0 | | 3x+3=x-18 | | -16=x-10 | | 24-6k=6(k-4) | | 0.4y+0.65x=60 | | 24-6k=6k(4-k) | | 6(1+4a)=-114 | | 3(9y+3)-9=2y+21 | | 39+0.75x=x | | (4z+2)+(5z-3)= | | T*4-3=12 | | 5x^2+10x+46=0 | | 14=-0.5x^2+46 | | 3(4x-1)=9x+6 | | 18x-6=20x-12 | | A*5+6=10 | | -30de+12=18d | | 5t+6-2r=7r-10 | | y+9x^3y=0 | | 4x+1=4x-2 | | 3x-5x+3=x-7+10 | | -5(x+2)+3x=-5(x-3)+3x |

Equations solver categories